Delivery of large heterologous polypeptides across the cytoplasmic membrane of antigen-presenting cells by the Bordetella RTX hemolysin moiety lacking the adenylyl cyclase domain - Holubova, Jana; Kamanova, Jana; Jelinek, Jiri; Tomala, Jakub; Masin, Jiri; Kosova, Martina; Stanek, Ondrej; Bumba, Ladislav; Michalek, Jaroslav; Kovar, Marek; Sebo, Peter (Infection and immunity, 2012)
The Bordetella adenylate cyclase toxin-hemolysin (CyaA; also called ACT or AC-Hly) targets CD11b-expressing phagocytes and translocates into their cytosol an adenylyl cyclase (AC) that hijacks cellular signaling by conversion of ATP to cyclic AMP (cAMP). Intriguingly, insertion of large passenger peptides removes the enzymatic activity but not the cell-invasive capacity of the AC domain. This has repeatedly been exploited for delivery of heterologous antigens into the cytosolic pathway of CD11b-expressing dendritic cells by CyaA/AC(-) toxoids, thus enabling their processing and presentation on major histocompatibility complex (MHC) class I molecules to cytotoxic CD8(+) T lymphocytes (CTLs). We produced a set of toxoids with overlapping deletions within the first 371 residues of CyaA and showed that the structure of the AC enzyme does not contain any sequences indispensable for its translocation across target cell membrane. Moreover, replacement of the AC domain (residues 1 to 371) with heterologous polypeptides of 40, 146, or 203 residues yielded CyaAΔAC constructs that delivered passenger CTL epitopes into antigen-presenting cells (APCs) and induced strong antigen-specific CD8(+) CTL responses in vivo in mice and ex vivo in human peripheral blood mononuclear cell cultures. This shows that the RTX (repeats in toxin) hemolysin moiety, consisting of residues 374 to 1706 of CyaA, harbors all structural information involved in translocation of the N-terminal AC domain across target cell membranes. These results decipher the extraordinary capacity of the AC domain of CyaA to transport large heterologous cargo polypeptides into the cytosol of CD11b(+) target cells and pave the way for the construction of CyaAΔAC-based polyvalent immunotherapeutic T cell vaccines.
Keywords: Animals; sekvenční delece; Toxoids; Cell Membrane; Dendritic Cells; dendritické buňky; Adenylate Cyclase Toxin; toxoidy; lidé; Protein Transport; rekombinantní proteiny; Antigen-Presenting Cells; Recombinant Proteins; Mice; CD8-Positive T-Lymphocytes; kultivované buňky; myši; transport proteinů; Cells, Cultured; antigen prezentující buňky; CD8-pozitivní T-lymfocyty; Male; zvířata; mužské pohlaví; Mice, Inbred C57BL; Sequence Deletion; buněčná membrána; adenylátcyklasový toxin; myši inbrední C57BL; Humans